Cost competitiveness of alternative maritime fuels in the new regulatory framework - Solakivi Tomi; Paimander Aleksi; Ojala Lauri (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
Shipping emissions are expected to grow together with world trade. For this reason, the European Union is targeting shipping emissions both by penalizing the use of fossil fuels and by creating incentives for the shipping sector to increase the role of alternative fuels. This research presents an estimate of when and with what assumptions low-carbon and carbon-neutral maritime fuels will be competitive against fossil fuels, while also examining what will be the cost impact on an individual vessel. The results show that the prices of low-carbon and carbon-neutral fuels are likely to remain high compared with fossil fuels, here assuming the currently planned regulation. The planned regulation, together with the estimated fuel price developments, will significantly increase fuel costs. The cost-optimal fuel path complying with the planned regulation is from fossil fuels via biofuels to electrofuels.